Physical Inactivity and Incident Depression in a Multiracial, Multiethnic Systemic Lupus Erythematosus Cohort. Issue 7 (29th April 2022) - Patterson, Sarah L.; Trupin, Laura; Yazdany, Jinoos; Dall'Era, Maria; Lanata, Cristina; Dequattro, Kimberly; Hartogensis, Wendy; Katz, Patricia
Abstract : Objective: Physical activity is known to improve depressive symptoms. The present study was undertaken to examine physical inactivity as a predictor of incident depression in systemic lupus erythematosus (SLE). Methods: Data derive from the California Lupus Epidemiology Study (CLUES), a longitudinal cohort with confirmed SLE diagnoses. Physical inactivity was assessed from a single item, "I rarely or never do any physical activities, " and depressive symptoms by the 8‐item Patient Health Questionnaire (PHQ‐8). Analysis included those not depressed at baseline (PHQ‐8 score <10) who completed an in‐person baseline assessment and at least 1 follow‐up visit (n = 225). Incident depression was defined as a PHQ‐8 score of ≥10 at follow‐up. Cox proportional hazards regression modeled incident depression over 2 years as a function of baseline physical inactivity, controlling for age, sex, race, income, comorbidities, disease activity, and disease damage. Results: At baseline, the mean ± SD age of the participants was 45 ± 15 years, 88% were female, and 70% identified as non‐White. Mean PHQ scores for those without depression at baseline did not differ by activity status, but those who were inactive at baseline were significantly more likely to develop depression over the next 2 years (hazard ratio [HR] 2.89 [95% confidence interval (95% CI) 1.46–5.71]). After adjusting for covariates, the association remained strong, including a >3‐fold increased risk of incident depression among the sedentary group (HR 3.88 [95% CI 1.67–9.03]). Conclusion: In this diverse SLE cohort, a simple question about physical inactivity was highly predictive of incident depression over the subsequent 2 years. Results suggest an urgent need for approaches to reduce sedentary behavior in this high‐risk population.